Reciprocal Effects Among Parental Homework Support, Effort, and Achievement? An Empirical Investigation - Xu, Jianzhong; Du, Jianxia; Wu, Shengtian; Ripple, Hailey; Cosgriff, Amanda (Frontiers in Psychology, 2018)
The present study investigates reciprocal influences of parental homework support, effort, and math achievement, using two waves of data from 336 9th-graders. Results revealed that higher prior autonomy-oriented support and homework effort resulted in higher subsequent achievement. Higher prior content-oriented support led to higher subsequent effort, but lower subsequent achievement. Additionally, higher prior effort led to higher subsequent autonomy-oriented support. Furthermore, our results supported the structural path invariance over gender. The current investigation advances extant research, by differentiating two forms of parental homework support (autonomy- and content-oriented support), and by showing their respective influences on subsequent homework effort and math achievement.